2021
DOI: 10.1140/epjqt/s40507-021-00103-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated radiation damage and thermal annealing of avalanche photodiodes

Abstract: Avalanche photodiodes (APDs) are well-suited for single-photon detection on quantum communication satellites as they are a mature technology with high detection efficiency without requiring cryogenic cooling. They are, however, prone to significantly increased thermal noise caused by in-orbit radiation damage. Previous work demonstrated that a one-time application of thermal annealing reduces radiation-damage-induced APD thermal noise. Here we examine the effect of cyclical proton irradiation and thermal annea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
(29 reference statements)
4
10
0
Order By: Relevance
“…This is a considerable challenge, due to the adverse effects of space radiation on detector dark count rates. However, using laser or thermal annealing techniques, QEYSSat is designed to plausibly maintain the dark count rate below that required for many quantum experiments [17], [18], [19]. Since the objective of the ongoing development is to demonstrate a quantum uplink to QEYSSat as an initial verification experiment, we use this section to summarize some important parameters of the QEYSSat mission [11] that impact the ground station design.…”
Section: Qeyssatmentioning
confidence: 99%
“…This is a considerable challenge, due to the adverse effects of space radiation on detector dark count rates. However, using laser or thermal annealing techniques, QEYSSat is designed to plausibly maintain the dark count rate below that required for many quantum experiments [17], [18], [19]. Since the objective of the ongoing development is to demonstrate a quantum uplink to QEYSSat as an initial verification experiment, we use this section to summarize some important parameters of the QEYSSat mission [11] that impact the ground station design.…”
Section: Qeyssatmentioning
confidence: 99%
“…Commencement of the QEYSSat mission in 2018 was preceded by several theoretical and experimental investigations into the mission's feasibility, both as a whole [31] and with focus on critical subsystems including pointing [32,33] and photon measurement [34,35]. Of these, one early work [36] numerically modelled the quantum optical link to establish the loss and fidelity of polarizedphoton transmission under the assumptions of the ex- pected orbital configuration and (generally conservative) atmospheric conditions.…”
Section: A System Configurationmentioning
confidence: 99%
“…However, the satellite method is not without problems. Satellites in LEO are exposed to radiation that can damage on-board Silicon Geiger-mode Avalanche Photodiodes (GM-APDs) [5][6][7][8][9][10], a key consequence of which is an increase in GM-APD dark count rate [8][9][10][11][12][13][14][15][16]. This is detrimental for operations involving single photons such as quantum key distribution, as the quantum bit error rate is proportional to the dark count rates.…”
Section: Introductionmentioning
confidence: 99%
“…Matters are further complicated when dopants and impurities react with vacancies and interstitials to form more complex defects with various energy levels [18]. Other GM-APD properties such as breakdown voltage, afterpulsing probability and timing jitter may also be affected by displacement damage, but prior studies have shown negligible changes [8,11,12,14,16]. Additionally, mean dark count rates may fluctuate between 2 or more levels, a phenomenon referred to as Random Telegraph Signals (RTS) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation